Penyuluhan Hukum Bebas Korupsi dan Tertib Administrasi Kepada Pemerintah Ohoi Ohoiren - Sarkol, Tarsius; Ayomi, Paulus Karmel; Ubwarin, Erwin; Ramschie, Jefta (Faculty of Law, Universitas Pattimura, 2021)
Introduction: Poor administrative management levels will lead to maladministration which leads to criminal acts of corruption, so there must be counseling on orderly administration and legal culture.Purposes of the Research: Community service at Ohoi Ohoiren is to improve administrative order in village management and enhance the legal culture Methods: In this service, we use community service methods, namely extension methods, design thinking, and role play.Results / Findings / Novelty of the Research: The people of the Kei Islands are still thick with traditional life, villages or Ohoi must be managed with good Ohoi governance, with good village administration system counseling and legal culture, it is hoped that the Ohoi Ohoiren community and Government can be better at using village funds and development in Ohoi.